Hidangan Buffet di Regular Event “Ramayana Night Market” Hotel Hyatt Regency Yogyakarta - Handayani Rahayuningsih; Bramanti Aditya (Jurnal Pariwisata Terapan, 2017)
Hyatt Regency Yogyakarta has strategies to increase the number of visitors to the hotel. One of the strategies made by Hyatt Regency Yogyakarta regular event “Ramayana Night Market" which is held every Saturday night.  The purposes of this research are to know the buffet menu and the layout of buffet in regular event “Ramayana Night Market” at Kemangi Bistro Hyatt Regency Yogyakarta. This research used observation, interview, and documentation techniques to collect the data. The results showed that the menu in regular event “Ramayana Night Market” are presented on the long table buffet and ranged from appetizer, main course, and dessert. Regular event “Ramayana Night Market” serve traditional food as concept. The layout of the buffet at regular event “Ramayana Night Market” is made to grouping the menu based on the type (appetizer, main course, and dessert) to make it easy for the customers to take the food from the buffet.